Role of Women in the Launch of Chandrayaan 3: Women's Contribution to the Success of Chandrayaan 3 (Journal of Advances and Scholarly Researches in Allied Education, 2023)
India's space program reached a major milestone with the launch of the Chandrayaan 3 mission,which followed in the footsteps of its successful lunar probes before it. Despite the stereotype that spacemissions are only the purview of males, this abstract reveals the many ways in which women contributedto the success of the Chandrayaan 3 mission. We take a look at the significant ways in which women wereinvolved in the development, planning, and implementation of the Chandrayaan 3 project. Women'sexperiences as scientists, engineers, project managers, and support workers are explored, since theywere crucial to the success of this mission. Chandrayaan 3 would not have been a success without theirhard work, knowledge, and creativity.